Hypothesis regarding the effects of gonadotropins on the level of free fatty acids and phospholipids in serum and follicular fluid during controlled ovarian stimulation. (February 2019) - Perovic, Milan D.; Sudar-Milovanovic, Emina M.; Simonovic, Ema D.; Resanovic, Ivana M.; Draganic, Veselin D.; Radakovic, Jovana D.; Soldatovic, Ivan A.; Isenovic, Esma R.
Abstract: Controlled ovarian stimulation (COS) is used to augment the number of retrieved oocytes in in vitro fertilization (IVF). Follicular fluid (FF) contributes significantly to oocyte quality. Since the FF is composed of follicular secretions and plasma exudation, it reflects alterations in granulosa and thecal cells secretion as well as changes in the level of plasma constituents. Phospholipids (PL) and free fatty acids (FFA) are important constituents of both, FF and serum. Our hypothesis is that COS affects the level of PL and FFA in serum. Furthermore, since the level of PL and FFA in FF partially depends on their levels in serum, as a collaterally of our hypothesis is that the existing level of PL and FFA in serum correlates with the levels of PL and FFA in FF, and that the dose of applied gonadotropins during COS will correlate with the levels of PL and FFA in serum and FF. In addition, we assume that the level of PL and FFA in serum and in FF after COS will correlate with the retrieved number of GQ oocytes, one of the most important outcomes of COS. .